Prospects for the Application of Unexplained Wealth Order in the Forfeiture of Assets Proceeds of Corruption in Indonesia - hakim, Ikhwanulhakim; Setiawan Noerdajasakti; Yuliati Yuliati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research focuses on discussing two things, namely (1) how the legal politics of regulating asset forfeiture for corruption crimes in Indonesia and (2) what are the prospects for applying the unexplained wealth order in asset forfeiture for corruption crimes in Indonesia. in this study it was found that: first, the legal politics of asset forfeiture for corruption crimes in Indonesia is still mainly oriented towards the process of asset forfeiture based on conviction, asset forfeiture can only be carried out if there is a judge's decision that is legally binding. However, if in the course of a criminal case there are difficulties in proof, the defendant dies in the judicial process, and after a court decision with permanent legal force it is known that there are assets or assets owned by the perpetrator that are the proceeds of crime, a civil lawsuit can be filed. however, it is different from the concept of unexplained wealth contained in the Criminal Asset Forfeiture Bill which has a broader dimension of civil filing.  And the filing of a civil lawsuit is not an alternative to the criminal justice process. Asset forfeiture lawsuits through the criminal process can be filed before, during and after criminal judgements, in order to avoid obfuscation and the disappearance and conversion of assets resulting from corruption crimes. Secondly, the prospect of implementing unexplained wealth in Indonesia has existed through the establishment and drafting of the Criminal Asset Forfeiture Bill. However, this bill is not equipped with the obligation to reverse the burden of proof, which is identical to the proof of ownership of assets contained in the Anti-Corruption Law. In the future, it is necessary to equalise the reversal of the burden of proof that should be carried out by the owner of the asset to facilitate the proof process and assist the legal apparatus.